ANALYSIS OF THE IMPACT OF COVID 19 AND THE POLICY OF IMPLEMENTING COMMUNITY ACTIVITIES LIMITATIONS ON MSMEs Central Jakarta in 2021 - Situmeang , Farida P; Dewi , Diana Setiyo; Alexandra , Esther Tiara (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2022)
This study aims to determine the impact of covid 19 and the policy of limiting the application of community activities (PPKM) on MSMEs in Central Jakarta in 2021. The Covid 19 and the policy of limiting the application of community activities as an independent variable, while MSMEs as the dependent variable. The population of this research is MSME actors. The type of research used is a quantitative type and the data used in this study is primary data in the form of respondents' answers to the questionnaire and processed using SPSS software version 28. Furthermore, the sampling technique used is census or total sampling with the number of respondents obtained by 100 actors. umkm in central jakarta. The results of the study based on the t test (Partial) proved that covid 19 and the policy of limiting the application of community activities to MSMEs had a significant positive effect. The calculated F test showed that the F Count was 7.340 and the sig. 0.001. When compared with Ftable 1.984, Fcount > Ftable and Sig value < 0.05. Thus showing that COVID-19 and restrictions on the application of community activities (PPKM) simultaneously affect MSMEs.